2019
DOI: 10.3390/app9245490
|View full text |Cite
|
Sign up to set email alerts
|

Sol-Gel Glass-Ceramic Materials Containing CaF2:Eu3+ Fluoride Nanocrystals for Reddish-Orange Photoluminescence Applications

Abstract: CaF 2 :Eu 3+ glass-ceramic sol-gel materials have been examined for reddish-orange photoluminescence applications. The transformation from precursor xerogels to glass-ceramic materials with dispersed fluoride nanocrystals was verified using several experimental methods: differential scanning calorimetry (DSC), thermogravimetric analysis (TG), X-ray diffraction (XRD), transmission electron microscopy (TEM), infrared spectroscopy (IR-ATR), energy dispersive X-ray spectroscopy (EDS) and photoluminescence measurem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…It was clearly visible that the intensities of bands A, B, and E decreased during the transformation of xerogels into glass-ceramics. Indeed, since Ca(CF 3 COO) 2 underwent thermal decomposition during controlled ceramization [ 41 ], the vibrations from the C–F bond disappeared for glass-ceramics, and bands A and B should have originated only from vibrations inside the Si–O–Si siloxane bridges. Further, a decrease in the intensity of band E clearly pointed to the conversion of Q 2 structural units into Q n (n = 3, 4) units as a consequence of polycondensation reaction.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It was clearly visible that the intensities of bands A, B, and E decreased during the transformation of xerogels into glass-ceramics. Indeed, since Ca(CF 3 COO) 2 underwent thermal decomposition during controlled ceramization [ 41 ], the vibrations from the C–F bond disappeared for glass-ceramics, and bands A and B should have originated only from vibrations inside the Si–O–Si siloxane bridges. Further, a decrease in the intensity of band E clearly pointed to the conversion of Q 2 structural units into Q n (n = 3, 4) units as a consequence of polycondensation reaction.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, such materials could be successfully predisposed for use in laser technologies [ 38 ], bio-imaging [ 39 ], or to increase the efficiency of solar cells [ 40 ]. Moreover, according to our previous results for sol-gel nano-glass-ceramics containing divalent metals fluorides, MF 2 (M = Ca, Sr, Ba), singly-doped with Eu 3+ ions, the most efficient segregation of Eu 3+ inside fluoride crystal lattice, was reported for the SiO 2 -CaF 2 system [ 41 , 42 , 43 ]. Indeed, a clear correlation was observed between the average decay time of the 5 D 0 state and growing difference in ionic radius of Eu 3+ and each of individual M 2+ cation in the following order: Ca 2+ → Sr 2+ → Ba 2+ (SiO 2 -CaF 2 :Eu 3+ : τ avg = 11.92; SiO 2 -SrF 2 :Eu 3+ : τ avg = 7.77; SiO 2 -BaF 2 :Eu 3+ : τ avg = 4.08 ms).…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…The method was tested using calcium fluoride (CaF 2 ) particles as a sample. CaF 2 finds a wide variety of applications in metallurgical, chemical, and optical materials industries [11]. Therefore, raw material quality is an essential part of process control.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18] Pawlik et al reported the fluorescence characteristics of Eu 3+ doped GCs containing CaF 2 / SrF 2 nanocrystals. 19,20 In 2006, the transparent SiO 2 -BaF 2 GCs doped with different content of Er 3+ were prepared by the sol-gel method by Daqin Chen. 21 As known, Ca, Sr, and Ba are in the same main group.…”
mentioning
confidence: 99%